Discrepancy in essential oil yield and root structure of vetiver across different storage periods: Essential oil and root structure of vetiver as affected by storage - Kumara, R Ravi; Prakash, T Arul; Yogendra, N D (Journal of Spices and Aromatic Crops, 2024)
The aromatic root of vetiver has immense potential for essential oil extraction, making handicraft products, and providing ecosystem services. Harvesting time and storage duration of harvested roots play a crucial role to obtain maximum quantity and superior quality essential oil. Moreover, the vetiver growers often store the harvested roots for up to four months. However, there were no standard recommendations with scientific evidence regarding the optimum storage duration for harvested vetiver roots. In this context, the present experiment was undertaken at the CSIR- CIMAP Research Centre, Bengaluru, to optimize the storage duration for economically viable production of essential oil. The experiment results revealed that roots stored for 7 days (from the harvesting day) yielded maximum quantity of essential oil (1.74±0.10) and that oil recovery decreased dramatically as storage days increased. Hence, distillation of vetiver roots within 30 days of harvest is advisable to obtain maximum returns. Further, the root anatomical observations over different storage durations revealed that the root tissue color changed from 7 days of storage to 90 days with tissue layers progressively loosening and detaching after 60 days of storage.